Impact of home garden interventions in East Africa: Results of three randomized controlled trials. (October 2021) - Depenbusch, Lutz; Schreinemachers, Pepijn; Roothaert, Ralph; Namazzi, Sylvia; Onyango, Charles; Bongole, Sophia; Mutebi, James
Highlights: There is a lack of evidence for impact of home garden interventions in Africa. We analyzed the impact of a home garden project in Kenya, Tanzania and Uganda. Results show only weak effects on household vegetable production. Results show no significant effect on vegetable consumption in the month of the survey. There is a need to better understand barriers to home garden interventions in Africa. Abstract: Sub-Saharan Africa has the lowest per capita consumption of vegetables of all regions in the world. As low vegetable consumption is associated with poor human health, there is need for effective policies and interventions to increase it. Home garden interventions have proven effective in several countries in Asia, but evidence from large trials is scant in Africa. Using data from a home garden promotion project in Kenya, Tanzania and Uganda, this study tests the hypothesis that home garden interventions, offered to rural households with women 14–35 years of age and/or with children under five years of age, increase household production and consumption of vegetables. Three randomized controlled trials collected pre- and post-intervention data (2 years apart) for 1, 255 intervention and control households. We report intent-to-treat effects and the treatment effect on the treated and analyze distributional effects using quantile regression. For Tanzania, the results show a 20% increase in households producing vegetables and an additional two months of vegetable harvesting, but no such significant effects were found for Kenya and Uganda. We find no significant effects on diets. Lack of impact may be explained from the fact that many participating households were already producing vegetables (reducing the scope for impact) and a low participation rate of selected households in training events. These results stand in contrast to the positive impacts of home garden interventions in Asia. The results suggest a need to better understand barriers to home garden interventions in the three countries and a need for more careful design, local adaptation and targeting.